Peran Dan Strategi Perusahaan Multinasional Dalam Pembangunan Ekonomi: Studi Kasus Nestle Indonesia - Bagus Hendra Stia Pratama; Priska Ananda; Ridho Cahya Lindiastuti; Sarpini Sarpini (Journal Economic Excellence Ibnu Sina, 2024)
This article discusses the role and strategies of multinational companies, with a focus on Nestlé Indonesia, in supporting economic development. Nestlé, as an example of a multinational company, operates in various countries and contributes to local economic growth through investment and innovation. This research identifies the scope of multinational companies and the strategies implemented by Nestlé in facing global challenges and complying with international regulations. In addition, this article highlights the importance of appropriate regulations to support the existence of multinational companies in the global market, as well as their positive impact on the national economy.